Megazol and its bioisostere 4H-1,2,4-triazole: comparing the trypanocidal, cytotoxic and genotoxic activities and their in vitro and in silico interactions with the Trypanosoma brucei nitroreductase enzyme - Carvalho, Alcione Silva de (2014)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Biologia Celular. Departamento de Síntese de Fármacos, Farmanguinhos. Rio de Janeiro, RJ, Brasil.